2005
DOI: 10.1101/gad.1366405
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of def selectively up-regulates Δ113p53 expression to arrest expansion growth of digestive organs in zebrafish

Abstract: Transcription factor p53 forms a network with associated factors to regulate the cell cycle and apoptosis in response to environmental stresses. However, there is currently no direct genetic evidence to show if or how the p53 pathway functions during organogenesis. Here we present evidence to show that the zebrafish def (digestive-organ expansion factor) gene encodes a novel pan-endoderm-specific factor. A loss-of-function mutation in def confers hypoplastic digestive organs and selectively up-regulates the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(267 citation statements)
references
References 52 publications
11
251
1
4
Order By: Relevance
“…58 The authors determined that D113p53 expression is regulated by def (digestive-organ expansion factor) gene. A loss-of-function mutation in def confers hypoplastic digestive organs and selectively upregulates the expression of D113p53 but not p53, resulting in compromised organ growth in def mutant Zebrafish.…”
Section: Conservation Through Evolution Of the P53 Gene Structurementioning
confidence: 99%
See 1 more Smart Citation
“…58 The authors determined that D113p53 expression is regulated by def (digestive-organ expansion factor) gene. A loss-of-function mutation in def confers hypoplastic digestive organs and selectively upregulates the expression of D113p53 but not p53, resulting in compromised organ growth in def mutant Zebrafish.…”
Section: Conservation Through Evolution Of the P53 Gene Structurementioning
confidence: 99%
“…This hypothesis is supported by two recent publications. The authors 58 report that a loss-offunction mutation in def gene in Zebrafish confers hypoplastic digestive organs and selectively upregulates the expression of D113p53 (homologue of human D133p53) but not p53. The increased expression of D113p53 selectively induces the expression of p53-target genes involved in cell cycle arrest but not in apoptosis, resulting in compromised organ growth in def mutant Zebrafish.…”
Section: Biological Activities Of P53 and Its Isoformsmentioning
confidence: 99%
“…Recently, one of these isoforms has been shown to have a distinct and critical function in the development of the gut of zebra fish. 44 There is now clearly more to learn.…”
Section: The Core Control Of P53mentioning
confidence: 99%
“…We conclude that even though p53 knockdown effectively minimizes the pleiotropic effects associated with Sbds knockdown, it is unable to rescue Sbds ATG MO-induced organogenesis phenotypes. 113p53 (human) is both a shortened isoform and target gene of full-length p53 (Chen et al, 2005;. Although full-length p53 is dispensable for normal development, work in the zebrafish mutant def (digestive organ expansion factor, or diexf) has demonstrated that 113p53 plays an important role in endoderm development.…”
Section: Loss Of P53 Does Not Rescue the Sbds Organogenesis Phenotypesmentioning
confidence: 99%